Water and suspended sediment division at a stratified tidal junction. Issue 3 (25th March 2013) - Buschman, F. A.; van der Vegt, M.; Hoitink, A. J. F.; Hoekstra, P.
Abstract : [1] Tidal junctions play a crucial role in the transport of water, salt, and sediment through a delta distributary network. Water, salt and sediment are exchanged at tidal junctions, thereby influencing the transports in the connecting branches and the overall dynamics of the system. This paper presents observations of water, salt and sediment transports in three channels that connect at a stratified tidal junction. Flow variation in one channel was found to lag behind flow variation in a connected channel by more than 1 h, which is largely attributed to channel length differences from the junction to the sea. The water columns in the three channels were periodically stratified during spring tide, whereas the salinity structure represented a salt wedge during neap tide. Salinity differences between the three channels were substantial. The channels contain water bodies of different salinity and act largely independently. Flow velocities in the upper and lower layers differed substantially. Flow in the lower layer was generally in the direction of acceleration produced by the baroclinic pressure gradient. Interestingly, baroclinic pressure gradients were sometimes directed landward, indicating the presence of saltier water at the land side of the estuary. In sharp channel bends close to the junction, secondary flow was strongest at the highest axial flow velocity during spring tide. In one channel bend, these circulations steered the suspended sediment toward the inner bend, which affected the suspended sediment division. Key Points: Flow phase differences affect water and salt transports at a tidal junction Secondary flow controls sediment division close to a junction Close to a tidal junction salinity may increase landwards